Variation of morphology, isozymic and vitamin C content of dragon fruit varieties - BANATI RAHMAWATI; EDWI MAHAJOENO (Smujo International, 2009)
Rahmawati B, Mahajoeno E. 2009. Variation of morphology, isozymic and vitamin C content of dragon fruit varieties. Nusantara Bioscience 1: 131-137. The aims of the research was to study the variation of morphology, the band pattern of isozyme, and vitamin C content of dragon fruit (Hylocereus spp.) varieties such as super red, red and white from Pasuruan (East Java), Sukoharjo and Klaten (Central Java), and Bantul districts (Yogyakarta). Morphological character were carried include fruit, stem, and flowers of each variety of dragon fruit. The isozymic pattern was analyzed using NTSYS 2.02i. The data matrix was counted based on the DICE coefficient. The clustering was done by applying UPGMA which counted through SHAN. Vitamin C content measured by titration method then analyzed descriptively. The results showed that the higher vitamin C content was found from super red of Pasuruan (6.00) and then followed by red color (5.376) and super red (5.113) both from Bantul. The morphological variation on the stem and petal colors, and fruits were also shown by the isozymic data of three varieties of dragon fruits collected from four separated locations. Esterase (EST) showed 18 bands and forming four (4) groups based on 75% genetic similarity index. The specific band occurred on Rf 0.633 of red varieties of dragon fruit from Bantul and on Rf 0.755 from Pasuruan. The specific band also occurs on Rf 0.347 of white variety from Bantul and on Rf 0.510 and on Rf 0.633 from Klaten. Glutamic oxaloacetic transaminase (GOT) enzyme shows 12 bands and also forming four groups with a little difference for member in the fourth group. The specific band occurs on Rf 0.321 of red color fruit from Pasuruan. The specific band also occurs on the white from Pasuruan on Rf 0.446 and on Rf 0.482. The variation of dragon fruits were also supported by isozymic data indicated that the morphological character were in accordance with the genetics data.